2023
DOI: 10.2147/phmt.s401461
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Guillain–Barré Syndrome in a Resource Limited Setting: Clinical Features, Diagnostic and Management Challenges, and Hospital Outcome

Abstract: Background Guillain–Barré syndrome (GBS) is an acute immune-mediated peripheral neuropathy with a highly variable clinical course and outcome. There remain diagnostic and treatment challenges in resource limited settings. This study aimed to describe the clinical presentation, diagnostic and management challenges, and hospital outcome of children with GBS in southern Ethiopia. Methods A retrospective chart review of children aged ≤14 years who were admitted with a diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Among these pediatric GBS, most (26/31, 83.8%) were aged ≤4 years old, which is similar with a Chinese study that the incidence of the GBS peaked in children aged 1–4 years. 16 It is reported that 17 children with GBS was more common in male, while 58% (18/31) of pediatric GBS was female in our reviewed cases. The clinical symptoms of GBS vary remarkably, and young age children with GBS often present with nonspecific clinical features which may lead to misdiagnosis and delayed diagnosis.…”
Section: Discussionmentioning
confidence: 75%
“…Among these pediatric GBS, most (26/31, 83.8%) were aged ≤4 years old, which is similar with a Chinese study that the incidence of the GBS peaked in children aged 1–4 years. 16 It is reported that 17 children with GBS was more common in male, while 58% (18/31) of pediatric GBS was female in our reviewed cases. The clinical symptoms of GBS vary remarkably, and young age children with GBS often present with nonspecific clinical features which may lead to misdiagnosis and delayed diagnosis.…”
Section: Discussionmentioning
confidence: 75%